2021
DOI: 10.2147/hiv.s296170
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lipid Profiles of Patients Taking Efavirenz-Based Antiretroviral Regimen Compared to Ritonavir-Boosted Atazanavir with an Optimized Background at Zewditu Memorial Hospital, Addis Ababa, Ethiopia

Abstract: Background Dyslipidemia represents significant health care concerns in patients taking antiretroviral therapy due to their association with cardiovascular disease risk. There is limited data regarding the effects of boosted atazanavir (ATV/r) treatment in the lipid profiles of Ethiopian HIV patients. Thus, this study compares the mean values of lipid profile differences of HIV patients on ATV/r-based regimen compared to efavirenz (EFV)-based regimen, while the background is Tenofovir Disoproxil Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
7
1
Order By: Relevance
“…Indeed, with the exception of HDL-C and Lp(a), higher mean values of each serum lipid profiles were observed in HIV patients on INSTIs regimen compared with those on NNRTIs regimen. The present study is inconsistent with earlier studies conducted in Ethiopia, indicating that HIV-infected patients undergoing long-term ART regimen are more likely to have elevated HDL-C as compared with patients undergoing short-term ART regimen ( 24 , 25 ). Additionally, the present study failed to confirm the findings of the SCRIPT trial, which was significantly associated with elevated Lp(a) levels ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, with the exception of HDL-C and Lp(a), higher mean values of each serum lipid profiles were observed in HIV patients on INSTIs regimen compared with those on NNRTIs regimen. The present study is inconsistent with earlier studies conducted in Ethiopia, indicating that HIV-infected patients undergoing long-term ART regimen are more likely to have elevated HDL-C as compared with patients undergoing short-term ART regimen ( 24 , 25 ). Additionally, the present study failed to confirm the findings of the SCRIPT trial, which was significantly associated with elevated Lp(a) levels ( 14 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Even though there was a wide range of confounding factors and limited sample size in this study, advanced methods and sensitivity analyses were used to obtain robust analysis results. Our findings confirm and extend the results from previous observational studies, which showed that age, gender, BMI, CD4 count, and ART duration were the predictors of unfavorable lipid profiles alterations in patients on ART ( 24 , 25 , 30 , 31 ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies (mostly done in HIV+ adults) have linked the use of protease (PI)-based ART with increased dyslipidaemia ( Cunha, 2015 ; De Lima et al., 2018 ; Irira et al., 2020 ; Belete et al., 2021 ; Hamooya et al., 2021 ; Tilahun et al., 2021 ). HIV+ individuals on PI-based regimen are more likely to have higher concentrations of triglycerides than those who were on non-PI therapies ( Kazooba et al., 2017 ; Belete et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (mostly done in HIV+ adults) have linked the use of protease (PI)-based ART with increased dyslipidaemia ( Cunha, 2015 ; De Lima et al., 2018 ; Irira et al., 2020 ; Belete et al., 2021 ; Hamooya et al., 2021 ; Tilahun et al., 2021 ). HIV+ individuals on PI-based regimen are more likely to have higher concentrations of triglycerides than those who were on non-PI therapies ( Kazooba et al., 2017 ; Belete et al., 2021 ). In this study, we similarly observed that CLWH receiving protease-based therapy (lopinavir boosted with ritonavir) had moderately higher triglyceride levels than CLWH who were on dolutegravir, an integrase-based regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In a resource-limited setting, Efavirenz (EFV) and Atazanavir/Ritonavir (ATV/r) serve as a backbone of combination antiretroviral regimens [ 16 ]. In Ethiopia, during the study period, the preferred first-line regimen for adults was EFV-based cART, specifically a combination of tenofovir (TDF), lamivudine (3TC), and EFV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%